Case report: Dynamic antibody monitoring in a case of anti-recombinant human erythropoietin-mediated pure red cell aplasia with prolonged course after kidney transplantation - Chen, Xiao-Mei; Li, Hui; Wu, Yu; Wang, Lan-Lan; Bai, Yang-Juan; Shi, Yun-Ying (Frontiers in Immunology, 2022)
Anti-erythropoietin (anti-EPO) antibody-mediated pure red cell aplasia (PRCA) is a rarely seen disease. Anti-EPO antibodies were mostly found in patients with chronic kidney disease who received recombinant human erythropoietin (rHuEPO) injections subcutaneously. The treatment against anti-EPO antibody-mediated PRCA included discontinuation of rHuEPO, immunosuppressive agents, intravenous immunoglobulin, plasmapheresis, or kidney transplantation. We reported a case of kidney transplant recipient with anti-EPO antibody-mediated PRCA, who had no trend of recovery after stopping rHuEPO, receiving regular induction and maintenance immunosuppressive regimens. He was further given 6 consecutive plasmapheresis sessions, cyclophosphamide, and adjusted maintenance immunosuppressive regimen into cyclosporine, sirolimus and prednisone. We monitored his anti-EPO antibody levels with a self-created simple mixing test. At 10 months post kidney transplant, his anti-EPO antibody finally turned negative, and his reticulocyte count dramatically increased. Cyclosporine, sirolimus and prednisone combined with roxadustat eventually alleviated the patient’s anti-EPO antibody-mediated PRCA. Our self-created simple mixing test for anti-EPO antibody titer was very helpful in disease monitoring and therapeutic guidance.